Upaya Penerapan Literasi Syariah pada Karyawan di Prathom Sangkhom Islam Wittaya School Sadao Songkhla Thailand - Suci Ramadhani; Munawir Munawir (Departement of Mathematics Education, 2023)
The purpose of this research is to find out how employees at Prathom Sangkhom Islam Wittaya School Sadao Songkhla Thailand are taught sharia literacy. This study uses a technique that is different from the quantitative methodology. One independent variable and one dependent variable are used in this study. Efforts to apply Islamic literacy are the independent variables of this research, and employees are the dependent variables of this research. The population of this research is a number of employees of Prathom Sangkhom Islam Wittaya School. Slovin scale and purposive sampling technique were used to select the sample, and the researcher classified the respondents according to the research needs. The data used in this study come from primary and secondary sources. In this review, surveys are used to collect data about respondents, as well as perceptions and encounters. The analyst conducts several information tests to assess the information collected, including the legitimacy test, the unshakable quality test, the old-style presumption test, the speculation test, and the basic direct reciprocity investigation. This study concludes that Ha is accepted and H0 is rejected based on a tcount value of 2.995 above table 1.70113 and a significance level of 0.006 0.05. It can be interpreted that the staff of the Wittaya Prathom Sangkhom Islamic School in Sadao, Songkhla, Thailand, at the same time have a significant impact on reading literacy.